Prevalence of seizures and associated factors in children under five living in a deprived municipality of southern Brazil Prevalência de convulsões e fatores associados em crianças menores de cinco anos em município pobre do sul do Brasil - Cheple Roberto Abib; Raúl A. Mendoza-Sassi; Jaime Bech-Nappi; Airton Tetelbom Stein (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the frequency and distribution of seizure in children under five, living in a deprived community. METHOD: This was a cross-sectional study, conducted in a probabilistic sample of 487 children aged 5 or less, resident in the rural and urban areas of São José do Norte, a poor municipality in southern Brazil, during the period 1998-99. Children were identified as having this disorder after the application of the three subsequent instruments, the screening questionnaire for epileptic seizures (SQES), the neurological diagnostic interview for epilepsy (NDIE) and the EEG. Statistical analysis included a multivariate analysis using Poisson regression. Prevalence ratios (PR) and 95% confidence intervals (CI) were calculated. RESULTS: Diagnosis of epileptic seizures was confirmed in 22 children. Prevalence of seizure was 45.2/1000 (CI 2.9-6.8). Absence of tap water (PR 2.86; IC 1.15-7.10), and precarious housing (PR 2.50; CI 1.01-6.18) were significantly associated with the outcome. CONCLUSION: Prevalence of seizure in this deprived population is extremely high and related to socio-economic conditions. OBJETIVO: Determinar a freqüência e distribuição de convulsões em crianças menores de cinco anos que vivem em uma comunidade pobre no sul do Brasil. MÉTODO: Foi realizado estudo de corte transversal, em amostra de 487 crianças menores de cinco anos de idade, residentes na área urbana e rural do município de São José do Norte, RS, Brasil, em 1988 e 1999. As crianças foram identificadas como positivo para a doença depois da aplicação de três instrumentos subseqüentes, rastreamento neurológico para epilepsia (QRN-E), entrevista diagnóstica neurológica para epilepsia (EDN-E) e eletrencefalograma. A análise estatística incluiu a análise multivariada por meio da regressão de Poisson. As razões de prevalência (RP) e intervalo de confiança (IC) de 95% foram calculados. RESULTADOS: O diagnóstico para crise epiléptica foi confirmado em 22 crianças. A prevalência de convulsões foi 45,2/1000 (IC 2,9-6,8). A ausência de água encanada (RP 2,86; IC 1,15-7,10) e moradias precárias (RP 2,50; IC 1,01-6,15) foram, significativamente, associadas com a convulsão. CONCLUSÃO: A prevalência de convulsão em uma população pobre é extremamente alta e relacionada a condições sócio-econômicas.